Subadventitial dismembered pyeloureteroplasty - new surgical technique for correction of uretero-pelvic junction stenosis - Akif Memmedoglu Bagirov (National Scientific Medical Center, 2021)
Objective: Open or laparoscopic dismembered pyeloplasty has been the gold standard for the correction of ureteropelvic junction obstruction (UPJO) with a success rate of about 90%. Main insufficient feature of dismembered pyeloureteroplasty is interfering ureteral blood supply, which creates the prerequisites for the deterioration of the regeneration of the ureter and the possibility of developing restenosis. Methods: We offered and applied the new method - subadventitial resection of ureteropelvic junction (UPJ) to prevent damage to vessels of the distal part of pelvis and proximal part of the ureter. The protection of blood supply in this area should improve anastomosis regeneration and prevent fibrotic changes for long time, simultaneously providing better condition for the kinetic ability of the ureter.  Results: Retrospective analysis of 106 patients with hydronephrosis, whom performed 108 open dismembered pyeloplasty (two patients were operated bilaterally) with subadventitial resection of UPJ from 1998-2020 years with a mean follow-up of 36 month shows that this technique has advantages over analogues. Conclusion: Our 22 years of experience shows that the technique of subadventitial resection of the ureter, allows us to save the ureteral blood circulation and thus creates conditions for better regeneration of the anastomosis and prevent later complications of dismembered pyelouretereroplasty.